The consequences of climate change for dryland biogeochemistry - Osborne, Brooke B (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation. This article has been contributed to by US Government employees and their work is in the public domain in the USA.